The anthropomorphization of AI and the concept of Buddhist compassion in human-machine interaction - Miao, Fangyan (Frontiers in Psychology, 2026)
IntroductionWith the advancement of anthropomorphic technologies and affective computing, the symbiosis of values between robots and humans has emerged as a crucial research topic. Against the backdrop of global cultural diversity, the four immeasurables—Metta (ci), Karuna (bei), Mudita (xi), and Upekkha (she)—in Buddhism offer a more adaptable and flexible ethical framework compared to other religious doctrines for guiding robotic development.MethodsBy comparing with other religious ethics, it demonstrates the unique feasibility of Buddhist compassion in shaping robots’ goodness-oriented behavior.ResultsTaking Guanyin, a quintessential symbol of compassion in Buddhism, as the moral archetype, the study proposes a design philosophy centered on equality, reciprocity, and responsibility. An illustrative case of elderly care robots showcases the practical application of this framework.DiscussionChallenges related to artificial compassion implementation and cultural disparities are also analyzed. The paper concludes that the cultural adaptability of Buddhist compassion in a cross-cultural context renders it a viable solution for harmonious human-robot symbiosis, integrating technological innovation with profound ethical wisdom.